2018
DOI: 10.3390/molecules24010118
|View full text |Cite
|
Sign up to set email alerts
|

Nanographene and Graphene Nanoribbon Synthesis via Alkyne Benzannulations

Abstract: The extension of π-conjugation of polycyclic aromatic hydrocarbons (PAHs) via alkyne benzannulation reactions has become an increasingly utilized tool over the past few years. This short review will highlight recent work of alkyne benzannulations in the context of large nanographene as well as graphene nanoribbon synthesis along with a brief discussion of the interesting physical properties these molecules display.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 129 publications
(204 reference statements)
0
53
0
Order By: Relevance
“…This method was also employed to furnish a series of larger PAHs, such as chrysene 52 and picene 54 [108]. Another widely used method is alkyne cyclization promoted by electrophilic reagents (Figure 11(c)) [109]. For example, Larock et al [110] reported ICl-induced intramolecular cyclization of 2-(arylethynyl)biphenyls (e.g., 55), providing PAHs with iodo groups, which can be used for further functionalizations.…”
Section: π-Extension With Extra Carbons and Ringsmentioning
confidence: 99%
“…This method was also employed to furnish a series of larger PAHs, such as chrysene 52 and picene 54 [108]. Another widely used method is alkyne cyclization promoted by electrophilic reagents (Figure 11(c)) [109]. For example, Larock et al [110] reported ICl-induced intramolecular cyclization of 2-(arylethynyl)biphenyls (e.g., 55), providing PAHs with iodo groups, which can be used for further functionalizations.…”
Section: π-Extension With Extra Carbons and Ringsmentioning
confidence: 99%
“…[60] Ad etailed review about this reaction and the different conditions used has been recently published. [61] An example of the use of the intramolecular alkyne benzannulation for the synthesis of alow band gap GNR has been reported by Chalifouxsg roup in 2016. [62] Starting from ap oly(p-phenylene) with properly located alkyne moieties (10), they used am odified version of the Swagersi ntramolecular, acid-promoted electrophilic cyclization to obtain asoluble [5] A GNR 11.Atfirst, TFAwas used as the Bronsted acid, but only one cyclization proceeded due to the rigidification of the polymer backbone,r esulting in am uch higher barrier for the second cyclization.Astronger acid, trifluoromethanesulfonic acid (CF 3 SO 3 H), was needed to fully complete the second cyclization.A ne xcess of TFA (100 equivalents) leads to only traces of the doubly cyclized product, even after two days.When only CF 3 SO 3 Hwas used, side products and lower yields was observed.…”
Section: Alkyne Benzannulationmentioning
confidence: 99%
“…Chalifoux and coworkers recently used a bay‐region‐selective alkyne benzannulation reaction on different small PAHs to prepare nanographenes whose absorption spectra extend to the red region . Starting from properly functionalized pyrenes, they prepared pero‐ and teropyrene derivatives through a four‐fold benzannulation reaction using either InCl 3 or a Brönsted acid as the catalyst (Figure ) .…”
Section: Nanographenes and Graphene Nanoribbonsmentioning
confidence: 99%